Facial Subcutaneous Emphysema As A Rare Complication Of Tonsillectomy - Paul, Mark; Asmi, Najihah Hanim; Ibrahim, Rohaida; Omar, Eshamsol Kamar; Mohamad, Irfan (IIUM Medical Journal Malaysia, 2017)
Tonsillectomy is a very common procedure in Otolaryngology practice. Common complications include bleeding, which can be primary or secondary due to infection of the tonsillar bed. Subcutaneous emphysema after a tonsillectomy is very rare. We report a 19-year-old girl who developed cervicofacial subcutaneous emphysema several hours after tonsillectomy with successful conservative treatment outcome.